2014
DOI: 10.2217/fon.14.149
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Genes at 2q24 Gains as Candidate Oncogenes in hepatoblastomas

Abstract: These genes appear as candidates for hepatoblastoma tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…It was found that DAPL1 gene was downregulated in an in vitro cultured ovarian granulosa cell of pig [22], but upregulated in the endometrial stromal and epithelial cells under the treatment of lipopolysaccharide [23]. DAPL1 gene was found to be upregulated in nine hepatoblastomas patients [24]. Based on the expression dataset of TCGA-LIHC (Liver hepatocellular carcinoma) cohort, we also observed an enhanced DAPL1 gene expression in hepatocellular carcinoma tissues, compared to normal tissues (data not shown).…”
Section: Discussionmentioning
confidence: 81%
“…It was found that DAPL1 gene was downregulated in an in vitro cultured ovarian granulosa cell of pig [22], but upregulated in the endometrial stromal and epithelial cells under the treatment of lipopolysaccharide [23]. DAPL1 gene was found to be upregulated in nine hepatoblastomas patients [24]. Based on the expression dataset of TCGA-LIHC (Liver hepatocellular carcinoma) cohort, we also observed an enhanced DAPL1 gene expression in hepatocellular carcinoma tissues, compared to normal tissues (data not shown).…”
Section: Discussionmentioning
confidence: 81%
“…However, focusing on the analysis of individual CpGs, hepatoblastomas from both sets showed a slightly hypomethylated pattern only at the first CpG of the LINE-1 sequence when compared with the differentiated livers (p = 0.03802 for set #1 and p = 0.05174 for set #2; Figure 4 ). The copy number alteration profile for all samples of hepatoblastoma set #1 has been previously evaluated by array-CGH [ 32 ]; tumor samples with and without chromosomal alterations >100 kb were compared with control differentiated livers regarding the methylation levels of LINE-1. Significant differences in LINE-1 methylation levels were found again only for the first CpG site ( Supplementary Figure 3 ), which is slightly hypomethylated in hepatoblastomas with copy number alterations (p = 0.0057; the Kruskall-Wallis test also indicated a difference of p = 0.0166 between the groups at this CpG).…”
Section: Resultsmentioning
confidence: 99%
“…Using our non‐synonymous, rare variant prioritization strategy, a second variant was identified in GALNT5 . Literature review provided no evidence that this variant was contributing to the disease presentation, as the gene has only previously been associated with differing expression in pancreatic, liver, and gastric cancers (Caffrey et al, 2019; Guo et al, 2018; Rodrigues et al, 2014). In addition, although this variant was considered rare (MAF < 1%), it had been previously reported in the homozygous state in multiple individuals in the gnomAD database (v2.1.1 and v3).…”
Section: Discussionmentioning
confidence: 99%